Source and geological significance of Jurassic asphalt in the Ruoqiang Sag of Southeast Depression, Tarim Basin, Northwestern China - Lan, Xiaodong; Bai, Zhongkai; Yang, Youxing; Jiang, Zhenglong; Zhang, Jile (Frontiers in Earth Science, 2024)
The Southeast Depression of Tarim Basin has very low petroleum exploration degree, and currently no industrial oil and gas discovery was found. Plenty of hydrocarbon shows exist in the Ruoqiang Sag, where hydrocarbon sources and accumulation process are unclear. Only two potential Jurassic hydrocarbon source rocks develop in the Ruoqiang Sag, which are the Yangye (J2y) lacustrine mudstone of Middle Jurassic and the Kangsu (J1k) coal-bearing mudstone of Lower Jurassic. In this study, the Jurassic asphalt found in the QD1 well was used to explore the possible hydrocarbon source and forming process in the Ruoqiang Sag, combined with the source rocks of drilling core and outcrops by the oil source correlation and hydrocarbon accumulation geochronology. The asphalts have lower light and heavy rare earth fractionation than the J2y mudstone, and the ΣREE content, chondrite normalized curves, δEu and Y/Ho value are similar to those of the J1k mudstone, especially J1k coal.The n-alkane ratios of carbon preference index (CPI) and odd-to-even preference (OEP) of Jurassic asphalts are greater than 1.0, indicating that its source rock has experienced low thermal evolution. All Jurassic samples have similar source-related biomarker but different maturity-related parameters, and thermal evolution degree of asphalt is closer to the J1k mudstone and coal, but slightly higher than the J2y mudstone.Meanwhile, rhenium-osmium isotopes show the asphalts are formed in 192+30/-45 Ma, which is similar to J1k sedimentation time. Meanwhile, asphalts contain coal macerals, and should be derived from the asphaltene precipitated by J1k coal during the early coalification. The low abundances of 25-norbornanes with non-or slightly petroleum biodegradation degree, indicate the asphalt was generated relatively late and migrated into J2y Formation along faults, possibly accompanied by the striking activities of Altyn Tagh Fault during the Neotectonics movement. This study provides evidences for the J1k coal bearing strata serving as effective source rock in the Ruoqiang Sag, and increases confidence for Jurassic petroleum exploration in the Southeast Depression of Tarim Basin. Especially structural traps and lithological traps near hydrocarbon source stoves, where Jurassic strata were deeply buried and far from the Altyn Tagh Range, are favorable oil and gas exploration targets.